PREDICTORS OF IN-HOSPITAL LENGTH OF STAY IN NSTEMI PATIENTS - Ahmad Handayani; Andika Sitepu; Faisal Habib (Universitas Muhammadiyah Sumatera Utara, 2019)
As our population grows older, the rate of NSTEMI patients is rising. Risk stratification is an important process for patients with Non-ST Elevation Myocardial Infarction (NSTEMI). Global Registry of Acute Coronary Events (GRACE) scores in the best to predict mortality and myocardial infarction in NSTEMI Patients. On the other hand, NSTEMI Patients trends to be older with more co-morbidity. In this scenario, we need to predict the length of stay as it correlates with the patient's prognostic and cost. This study aims to analyze factors influencing the in-hospital length of stay in survivor NSTEMI Patients in four different hospitals (Adam Malik Medan National General Hospital, Pirngadi Medan General Hospital, Grandmed Lubuk Pakam General Hospital, and Aceh Tamiang Public General Hospital). This was an observational study with prospective design conducted on 44 patients in four different hospitals from March to May 2017. We only included the patients that discharged alive from the. hospital Statistical analysis was performed to assess the routine clinical and laboratory variables relations with the length of stay. Prolong length of stay was defined as more than 5 days. As mentioned in the previous study, older age, heart failure will prolong the length of stay. The limitations of this study were we didn't analyze the effect of revascularization, the co-morbidities, and the method of patient’s payment. We should use GRACE and TIMI risk score routinely, optimizing therapy for heart failure and giving special attention to elderly patients in NSTEMI Patients.Keywords: NSTEMI, GRACE, Length of Stay